Social and healthcare professionals’ experiences of end‐of‐life care planning and documentation in palliative care - Anne Kuusisto; Kaija Saranto; Päivi Korhonen; Elina Haavisto (Nursing Open, 2023)
Abstract Aim To explore social and healthcare professionals' experiences of end‐of‐life (EOL) care planning and documentation in palliative care. Design A qualitative study with narrative methodology. Methods A narrative method with interviews was used. Data were collected from purposively selected registered nurses (n = 18), practical nurses (n = 5), social workers (n = 5) and physicians (n = 5) working in palliative care unit in five hospitals in three hospital districts. Content analysis within narrative methodologies was undertaken. Results Two main categories – patient‐oriented EOL care planning and multi‐professional EOL care planning documentation– were formed. Patient‐oriented EOL care planning included treatment goals planning, disease treatment planning and EOL care setting planning. Multi‐professional EOL care planning documentation included healthcare professionals' and social professionals' perspectives. Healthcare professionals' perspectives on EOL care planning documentation included benefits of structured documentation and poor support of electronic health record (EHR) for documentation. Social professionals' perspective on EOL care planning documentation included usefulness of multi‐professional documentation and externality of social professionals in multi‐professional documentation. Conclusion The results of this interdisciplinary study demonstrated a gap between what healthcare professionals consider important in Advance Care Planning (ACP), that is, proactive, patient‐oriented and multi‐professional EOL care planning and the ability to access and document this in a useful and accessible way in the EHR. Relevance to Clinical Practice Knowledge of the patient‐centered EOL care planning and multi‐professional documentation processes and their challenges are prerequisites for documentation to be supported by technology. Reporting Method The Consolidated Criteria for Reporting Qualitative Research checklist was followed. Patient or Public Contribution No patient or public contribution.